“Lock to Live” for firearm and medication safety: Feasibility and acceptability of a suicide prevention tool in a learning healthcare system - Boggs, Jennifer M.; Quintana, LeeAnn M.; Beck, Arne; Clinch, Samuel; Richardson, Laura; Conley, Amy; Richards, Julie E.; Betz, Marian E. (Frontiers in Digital Health, 2022)
Objective Few patients with suicide risk are counseled on lethal means safety by health providers. This study tested the feasibility of different delivery methods for Lock to Live (L2L), a web-based decision aid of safe storage options for firearms and medications. Methods Patients reporting suicide ideation on the PHQ9 depression screener during outpatient health visits were included. Invitation messages to visit L2L were sent via combinations of email, text, Electronic Health Record (EHR) message, mailed letter, or provider referral, followed by a survey about storage behavior and acceptability. Provider interviews evaluated logistical considerations and acceptability. Results The population-based method reached 2,729 patients and the best method (EHR message plus 2 email reminders) had 11% uptake (L2L visitation rate). Provider referral had small reach (14 patients) and 100% uptake (all visited). Provider interviews identified several strategies to promote uptake including: EHR reminders, provider training, quality metrics with accountability, a clearly communicated lethal means screening/counseling policy, and strong organizational leadership support. Conclusion Despite the low uptake for population-based (11%), far more patients with suicide risk were engaged in the L2L tool through population-based outreach than provider-referral over the same time frame.